Assessing the Knowledge of Scabies Among the Women of a Rural Community at Lahore - Akbar, Naeema; Hanif, Asif; Gilani, Muhammad Amir gilani; Yasmin, Samina (International Journal of Social Sciences and Management, 2020)
Background: scabies is endemic in most of the mountainous areas of Pakistan, the crowded and unhygienic conditions in IDP (Internally Displaced Persons) camps immediately after the earthquake was the ideal environment for a full blown outbreak of epidemic proportions. Objective: The purpose of this study was to assess Knowledge of scabies among the women of a rural community at Lahore. Methodology: Descriptive cross sectional study design was conducted to assess the Knowledge of scabies among the women and a sample size of n=75 participants were selected for this study through convenient sampling. Data was collected from the women at Gajjumatta community Lahore. Result: The main findings were as following. 93.3% of the participants knew that scratching effect causes to Scabies, 73.3% had knowledge that Skin is the main affected organ involved in scabies and 86.7% had knowledge that itching at night and feeling heat is the main sign of scabies Conclusion: The purpose of this study was to assess Knowledge of scabies among women at Gajumatta in Lahore. Overall result shows a good knowledge among women of Gajumatta community. Int. J. Soc. Sc. Manage. Vol. 7, Issue-1: 30-37